Experimental Study on concrete with Partial Replacement of Cement and Fine Aggregate by Fly Ash and Marble Dust - Kumar, Niraj; Kumar Goyal, Pradeep (International Journal of Computer Sciences and Engineering, 2025)
The use of conventional concrete when used in large quantity takes more cost as compared to adapted concrete using the waste marble dust which is found from marble industries and fly ash found from thermal power plant. Also the compressive strength of concrete using marble dust and fly ash increases up to a certain extent which proves to be more economical. Cement is used in construction and it emits CO₂ in very huge amount which is harmful for environment. As the cement content in concrete going to be decrease so the sustainable development of environment takes place which in turn makes effective in terms of health of people.